Efektivitas Eye Movement Desensitizion And Resprocessing (EMDR) Butterfly Hugs Sebagai Self Healing Stres Kerja Perawat: Literature Review - Endah, Rika; Khairani, Ilma; Sari Rezeki, Purnama (JINTAN: Jurnal Ilmu Keperawatan, 2025)
Nurses are required to provide quality and excellent health services. Nurses are responsible for treating their patients until they recover psychologically. And have pressure and workload in a shift system. Such nursing conditions require nurses to carry out their responsibilities so that they can cause stress. The practice of psychotherapy called the EMDR butterfly hug should help nurses reduce stress. By using comforting thoughts, the butterfly hug is a therapy technique used to maintain emotional stability and calm the mind. The research method used is a narrative literature review of 11 references by taking from the Science Direct, Proquest, Ebsco and Google Scholar databases from 2019 to 2023 using the keywords "Eye Movement Desensitization and Resprocessing (EMDR) OR Butterfly Hugs OR EMDR Self Healing AND Nurse". The results of the study indicate that implementing the Butterfly Hugs and Eye Movement Desensitization and Resprocessing (EMDR) strategies can reduce self-healing work stressors for nurses. The analysis of the research method was widely studied using descriptive methods with a qualitative approach. The implementation of Eye Movement Desensitization and Resprocessing (EMDR) OR Butterfly Hugs OR EMDR Self Healing AND Nurse strategies can provide a reduction in work stressors and self-healing for nurses for the present and future.